Utilization of moringa oleifera seeds flour and starches of white yam, trifoliate yam and sweet potato in cookies - Obioma, Okereke Goodluck; Doshima, Igbabul Bibiana; Ikya, Joseph (International Journal of Food Science and Nutrition, 2021)
Native starches extracted from selected roots and tubers (white yam, trifoliate yam and sweet potato) were physically and chemically modified through heat moisture treatment and acetylation respectively while nutritious flour was processed from Moringa oleifera seeds. Composite flours of 85% wheat flour, 10% native/modified starch and 5% Moringa oleifera seed flour blends were developed for production of composite cookies. Nutritional compositions and baking properties of these composite cookies were investigated against those of control samples (i.e. 100% wheat flour cookies). Nutritionally, composite cookies were significantly (p<0.05) higher than control cookies while in terms of baking properties, the control cookies did not significantly (p<0.05) differ from composite cookies. Cookies sample NSPC (i.e. made from composite flour of 85% wheat flour: 10% native sweet potato starch: 5% Moringa oleifera seed flour) took lead positions in crude fat content (19.30%), protein content (13.25%), calcium content (121.95 mg/100g), iron content (3.75 mg/100g), vitamin A content (4.910 µg/g), vitamin B1 content (0.079 mg/100g), vitamin B2 content (0.112 mg/100g), vitamin B3 content (0.580 mg/100g), vitamin B6 (0.480 mg/100g) and vitamin C content (14.710 mg/100g). Though NTYC (cookies of composite flour of 85% wheat flour: 10% native trifoliate yam starch: 5% Moringa oleifera seed flour) and CTYC (cookies of composite flour of 85% wheat flour: 10% acetylated white yam starch: 5% Moringa oleifera seed flour) shared the highest moisture content of 8.20%, NTYC had highest values in ash content (2.60%) and spread factor (62.37)) and toddled in carbohydrate content (55.45%). CWYC (i.e. cookies of composite flour of 85% wheat flour: 10% acetylated white yam starch: 5% Moringa oleifera seed flour) had best values in storage-ability potential (i.e. lowest moisture content of 2.50%) and energy content (467.30 Kcal), but had lowest values in magnesium (57.31 mg/100g) and phosphorus content (64.18 mg/100g). The 100% wheat flour cookies (CTLC) led in carbohydrate content (63.35%), magnesium content (64.71 mg/100g) and phosphorus content (69.28 mg/100g) but lagged behind in ash content (1.70%), crude fat content (1.25%), protein content (11.75%), iron content (2.45%), vitamin A (2.250 µg/g), vitamin B1 (0.047 mg/100g), vitamin B2 (0.073 mg/100g), vitamin B3 (0.250 mg/100g), vitamin B6 (0.290 mg/100g), vitamin C (13.530 mg/100g) and spread factor (41.47). PWYC (cookies of composite flour of 85% wheat flour: 10% heat moisture treated white yam starch: 5% Moringa oleifera seed flour) recorded lowest values in crude fat content (17.80%) and energy value (441.30 Kcal); whereas PTYC (cookies of composite flour of 85% wheat flour: 10% heat moisture treated trifoliate yam starch: 5% Moringa oleifera seed flour) made lowest values in crude fibre content (1.60%) and calcium (117.31 mg/100g). NWYC (cookies of composite flour of 85% wheat flour: 10% native white yam starch: 5% Moringa oleifera seed flour).led in crude fibre content (1.73%) and general acceptability (8.07) while CSPC (cookies of composite flour of 85% wheat flour: 10% acetylated starch: 5% Moringa oleifera seed flour) scored lowest in general acceptability (6.20)
Keywords: wheat flour; nutritional compositions and baking properties; cookies; native and modified white yam/trifoliate yam/sweet potato starches; ACE: Food Technology and Research; Nigeria; Food tech and research; Benue University, kano